Epidemiology, clinical features and outcomes of patients with kidney biopsy proven IgA vasculitis in Auckland and Northland, Aotearoa, New Zealand presenting between 2003–2020. - Janak Rashme de Zoysa; Zhenqiang Wu (BMC Nephrology)
Abstract Aims Immunoglobulin A vasculitis is a small vessel vasculitis. Here we describe the epidemiology, clinical features, treatment and outcomes in patients, over the age of 16 years, with kidney biopsy proven cases seen in two regions of Aotearoa, New Zealand over an 18-year period. Methods Potential cases were identified, in patients over the age of 16 years, who underwent kidney biopsy between 2003 and 2020. A retrospective review of all potential cases was performed. Results Thirty-four patients were identified, 10 females and 24 males, of whom 15 were European, 5 Māori, 7 Pacific Peoples, and 7 Asians. The incidence was 1.16 per 1,000,000 patient-years (95% CI: 0.82–1.61), there was an excess in males (RR = 2.42 95% CI 1.16–5.06, p = 0.016) with no excess by ethnicity. Mean age at presentation was 42.8 years (range 16.4–70.5). Mean creatinine at presentation was 118µmol/L (range 51–410). Twenty-six patents received corticosteroids, with two patients also receiving cyclophosphamide and five patients receiving azathioprine. Six patients (17.6%) needed long-term kidney replacement therapy, 12 were left with significant chronic kidney disease (35.3%) and 4 died (11.8%) at the end of study follow up. Elevated serum creatinine at presentation was predictive of need for kidney replacement therapy. Age was predictive of mortality. Conclusions Immunoglobulin A vasculitis is not overrepresented among indigenous people in Aotearoa New Zealand. The majority of patients receive immunosuppression, however, were left with significant kidney disease.